Searching for pure iron in nature: the Chelyabinsk meteorite. Issue 89 (9th September 2016) - Leedahl, Brett; Korolev, Aleksander V.; Zhidkov, Ivan S.; Skornyakov, Sergey L.; Anisimov, Vladimir I.; Belozerov, Alexander S.; Kukharenko, Andrey I.; Kurmaev, Ernst Z.; Grokhovskii, Victor I.; Cholakh, Seif O.; Moewes, Alexander
Abstract : Herein we aimed to use thermomagnetic analysis (TMA) to determine the nature of iron and nickel in the Chelyabinsk meteorite, and their effect on the meteorite's magnetism. Abstract : Herein we aimed to use thermomagnetic analysis (TMA) to determine the nature of iron and nickel in the Chelyabinsk meteorite, and their effect on the meteorite's magnetism. Our magnetic measurements show that 3% of the meteorite is metallic and consists of two ferromagnetic phases with Curie temperatures of T C1 = 1049 K and T C2 = 800 K. Using an Fe–Ni phase diagram, we show that the lower of the two temperatures is due to an Fe–Ni alloy with 51% Ni, while the higher Curie temperature phase is due to a pure or nearly pure (Ni-free) iron phase, for which we can be certain the Ni content is less than 1%. X-ray absorption (XAS) measurements show there are two clearly distinct iron oxidation environments: metallic and 2+, with the 2+ regions differing significantly from the standard FeO phase. We also demonstrate that beneath the immediate surface, iron exists virtually entirely in a metallic state. We are then able to estimate the surface composition using XPS, for which we found that 10% of iron on the surface is still surprisingly unoxidized. Finally, our theoretical calculations show how the density of states for both Fe and Ni atoms is affected for different nickel concentrations.